2020
DOI: 10.1007/s10456-020-09736-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Murine Models of Cerebral Cavernous Malformations

Abstract: Cerebral cavernous malformations (CCMs) are ectatic capillary-venous malformations that develop in approximately 0.5% of the population. Patients with CCMs may develop headaches, focal neurologic deficits, seizures, and hemorrhages. While symptomatic CCMs, depending upon the anatomic location, can be surgically removed, there is currently no pharmaceutical therapy to treat CCMs. Several mouse models have been developed to better understand CCM pathogenesis and test therapeutics. The most common mouse models in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 77 publications
4
56
0
Order By: Relevance
“…Recent studies have emphasized that chronic models may be more reflective of the course of the human disease (17,(55)(56)(57). We therefore, investigated the expression of VEGF increased in perilesional astrocytes in juvenile Pdcd10 ECKO ;Vegfa tm1.1Nagy mice.…”
Section: Astrocyte-derived Vegf Increases During Ccm Formation In Juvenile Micementioning
confidence: 98%
“…Recent studies have emphasized that chronic models may be more reflective of the course of the human disease (17,(55)(56)(57). We therefore, investigated the expression of VEGF increased in perilesional astrocytes in juvenile Pdcd10 ECKO ;Vegfa tm1.1Nagy mice.…”
Section: Astrocyte-derived Vegf Increases During Ccm Formation In Juvenile Micementioning
confidence: 98%
“…For example, damaged ECs produce TXA2, which turns on platelet activation, adhesion and aggregation onto the vascular walls 59 . Activated ECs express ADAM-15, a transmembrane cell-surface protein and member of the ADAM (a disintegrin and metalloproteinase) family, prior to its binding and activation of platelets through the GIIb/IIIa receptor in the face of MI 60 . Taken together, endothelium damage-mediated platelet activation followed by coronary artery thrombosis are the major perceived pathogenic mechanisms underscoring MI.…”
Section: Coagulationmentioning
confidence: 99%
“…We therefore propose that astrocytes contribute to CCM disease by a non-cell-autonomous mechanism mediated by CCM endothelium-driven hypoxia and angiogenic programs.Our in vivo observations in the neonatal CCM animal model, using endothelial-specific inactivation of Pdcd10 or Krit1, revealed that lesion development is spatially restricted to zones of fibrous astrocytes, which are prevalent in the white matter of the CNS(46), and that the selective ablation of proliferative astrocytes(48) markedly reduced CCM lesion and an increase in VEGF expression, prompting the suggestion that a subset of proliferative astrocytes supports CCM lesions in the developing hindbrain. Moreover, our observations in the chronic CCM animal model(53,54), using brain endothelial-specific inactivation of Pdcd10(64), further revealed the high propensity of CCM lesions to develop surrounded by GFAP+ astrocytes throughout the CNS, including the cerebellum, cerebrum, and spinal cord. Earlier reports have shown that loss of Pdcd10 in neuroglia cells leads to formation of CCM lesions through non-cellautonomous mechanisms, implicating a role of neural cells in the CCM pathogenesis(17).…”
mentioning
confidence: 70%
“…The previous studies showed increased VEGF expression in an acute neonatal CCM model. Recent studies have emphasized that chronic models may be more reflective of the course of the human disease(5254). We therefore, investigated the expression of VEGF increased in perilesional astrocytes in juvenile Pdcd10 ECKO ;Vegfa tm1.1Nagy mice.…”
Section: Resultsmentioning
confidence: 99%